Modality-specific and modality-general electrophysiological correlates of visual and auditory awareness: Evidence from a bimodal ERP experiment - Filimonov Dmitri; Railo Henry; Revonsuo Antti; Koivisto Mika (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
To date, most studies on the event-related potential (ERP) correlates of conscious perception have examined a single perceptual modality. We compared electrophysiological correlates of visual and auditory awareness in the same experiment to test whether there are modality-specific and modality-general correlates of conscious perception. We used near threshold stimulation and analyzed event-related potentials in response to aware and unaware trials in visual, auditory and bimodal conditions. The results showed modality-specific negative amplitude correlates of conscious perception between 200 and 300 ms after stimulus onset. A combination of these auditory and visual awareness negativities was observed in the bimodal condition. A later positive amplitude difference, whose early part was modality-specific, possibly reflecting access to global workspace, and later part shared modality-general features, possibly indicating higher level cognitive processing involving the decision making, was also observed.